2022
DOI: 10.6065/apem.2142210.105
|View full text |Cite
|
Sign up to set email alerts
|

The effect of metformin on vitamin B12 level in pediatric patients

Abstract: Purpose: Metformin is a common medication for patients with hyperglycemia. In adults, one well-documented side effect of metformin is vitamin B12 deficiency. However, this side effect has rarely been studied in pediatric patients. This study examined the changes of vitamin B12 level in pediatric patients being treated with metformin.Methods: Data were collected from pediatric patients (n=151) with at least 3 months of consecutive metformin intake. The effects of dose of metformin on the mean vitamin B12 level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The results appear controversial. Some studies reported a lack of change in the vitamin B 12 concentrations of minors on MET treatment [ 24 , 25 , 26 ], whereas others suggested that greater MET doses and prolonged treatment duration were associated with lower vitamin B 12 concentrations [ 17 , 18 , 27 , 28 , 29 ], as suggested by the MHRA [ 23 ]. However, herein, the prevalence of vitamin B 12 deficiency greatly exceeded the rate proposed by the MHRA [ 23 ], with 18% of the sample treated with MET exhibiting total vitamin B 12 concentrations indicative of biochemical deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results appear controversial. Some studies reported a lack of change in the vitamin B 12 concentrations of minors on MET treatment [ 24 , 25 , 26 ], whereas others suggested that greater MET doses and prolonged treatment duration were associated with lower vitamin B 12 concentrations [ 17 , 18 , 27 , 28 , 29 ], as suggested by the MHRA [ 23 ]. However, herein, the prevalence of vitamin B 12 deficiency greatly exceeded the rate proposed by the MHRA [ 23 ], with 18% of the sample treated with MET exhibiting total vitamin B 12 concentrations indicative of biochemical deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The use of total serum vitamin B 12 concentrations as the only biomarker for the assessment of vitamin B 12 status is another limitation. Nonetheless, most of the studies available in the literature ( Table 3 ) also relied on serum vitamin B 12 levels only [ 17 , 24 , 25 , 26 , 27 , 29 , 31 ]. Furthermore, the diet record of participants is an important addition to the assessment of vitamin B 12 status, as most studies ( Table 3 ) only relied on hematological parameters, ignoring the importance of dietary intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most plausible mechanism is the alteration in the calcium-dependent binding of the intrinsic factor and vitamin B12 complex with the receptors in the terminal ileum ( 174 , 175 ). However, small short-term studies that included pediatric patients on Metformin for various indications did not demonstrate an association between metformin and vitamin B12 deficiency ( 176 , 177 ).…”
Section: Side Effects and Contraindicationsmentioning
confidence: 99%
“…In addition, dietary supplementation with vitamins E and D, polyunsaturated fatty acids, and probiotics has shown potential benefits of reducing liver inflammation and improving liver enzyme levels in pediatric patients with NAFLD and NASH. However, its long-term safety and efficacy in children and adolescents remain to be evaluated [ 8 , 9 ]. Metformin, an insulin-sensitizing agent, is not recommended for the treatment of NAFLD alone, although it is an important antidiabetic agent for controlling hyperglycemia.…”
mentioning
confidence: 99%